2015
DOI: 10.1186/s40337-015-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

“Time’s up” – staff’s management of mealtimes on inpatient eating disorder units

Abstract: BackgroundRefeeding and normalizing eating behaviour are main treatment aims for individuals admitted to inpatient eating disorder units. Consequently, mealtime activities are specific, everyday activities, serving a clear therapeutic purpose, despite numerous challenges for both staff and patients. Few studies have specifically addressed staff involvement, interactions, and management activities to structure mealtimes. In this study, we investigated the structure of mealtime activities on inpatient eating dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…The interviews indicated that the most important rule that influences staff collaboration, and division of labor in particular, was strategic seating. This is in line with what we found in our observations of the internal meal structure [15], where staff reserved or sought the middle seats during most of the observed meals, suggesting behavior in accordance with strong, interactive scripts. The analysis of the interviews supports the observation of scripted behavior by staff, and scripts can be a possible explanation for the seemingly implicit nature of staff collaboration during mealtimes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The interviews indicated that the most important rule that influences staff collaboration, and division of labor in particular, was strategic seating. This is in line with what we found in our observations of the internal meal structure [15], where staff reserved or sought the middle seats during most of the observed meals, suggesting behavior in accordance with strong, interactive scripts. The analysis of the interviews supports the observation of scripted behavior by staff, and scripts can be a possible explanation for the seemingly implicit nature of staff collaboration during mealtimes.…”
Section: Discussionsupporting
confidence: 91%
“…The empirical findings reported in this paper is drawn from interview data, which is part of a larger data corpus of video recorded observations of mealtimes and interviews with participating staff members, focusing on teamwork and interaction during mealtimes on EDUs. Data from video-recorded observations exploring the internal structure in a meal and from interviews and video observations exploring staff behavior in staff – patient interactions have been published elsewhere [14, 15]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a multimodal, multidisciplinary approach underpins inpatient treatment (Bakker et al, 2011;Hage, Rø, & Moen, 2015), facilitating healthy friendships on wards has received little attention. While clinicians have observed the negative impact of peers on engagement with treatment (Ramjan & Gill, 2012), young people have identified fellow patients as a key source of support (Offord, Turner, & Cooper, 2006).…”
Section: Introductionmentioning
confidence: 99%